Pengembangan E-Modul Menggunakan Genially untuk Meningkatkan Hasil Belajar pada Materi Tradisi dan Budaya Masyarakat di Sekitarku - Fani Vanesa; Fitri Anjaswuri; Ade Wijaya (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The use of digital teaching materials at SDN Bantarkemang 6 is still limited and lacks variety, causing students to experience difficulties in understanding the topic of Traditions and Culture of the Surrounding Community, resulting in low learning outcomes. This study aimed to develop a Genially-based E-Module on this topic and determine its validity, practicality, and effectiveness in improving students' learning outcomes. The study employed the Research and Development (R&D) method using the ADDIE development model. The participants were 27 fourth-grade students of Class IV B at SDN Bantarkemang 6. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning outcome tests. The validation scores were 93,33% from the media expert, 100% from the material expert, and 92% from the language expert, with an average of 95.11%, categorized as very valid. Student and teacher responses were 89.09% and 100%, respectively, with an average of 94.54%, categorized as very practical. The product's effectiveness was indicated by an N-Gain score of 0.77, categorized as high. Therefore, the Genially-based E-Module was found to be very valid, very practical, and effective in improving students' learning outcomes.